Prevalence of Partial Edentulousness Among The Bangladeshi Adults (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: The study was done to determine the occurrence of various missing teeth pattern among the partial edentulous patients residing in Chattogram district of Bangladesh. Study was undertaken from January to August 2018.  Materials and methods: The design was a descriptive cross-sectional study. Two hundred and thirty three persons aged between 13 and 87 years (106 males and 127 females) were included, intraoral examination was done visually and results were recorded on specially designed clinical examination forms. Data were analyzed using statistical package SPSS 19.0 version to investigate the relationship between quantitative variables.  Results: The results showed the patients with Kennedy's Class III were found to be the most prevalent among all the groups (38.67%). The most common modification in all the groups was Class III modification I (14.5%).  Conclusion: The findings of this study show that the Kennedy's Class III was the most commonly occurring and were found to be more predominant in the younger group of population.JCMCTA 2020 ; 31 (1) : 120-124